2016
DOI: 10.1016/j.jvs.2016.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch involvement worsens the prognosis of type B aortic dissections

Abstract: AD-arch dissections are associated with a higher risk of cardiac and neurologic events, need for early intervention, and dissection-related death than AD-desc dissections. Because further proximal dissections into the ascending aorta were rare in this study, medical management appears to be safe as the initial treatment of AD-arch dissections. However, surgeons should be aware of the increased risk of complications and the potential need for urgent interventions in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Only one of these studies showed a significant association with outcomes (lower rate of AE and intervention). 45 In contrast, the proximal extension to the arch predicted both mortality and surgical intervention in two studies, 9,50 and was nonsignificant in another two. 22,37 Conversely, Kamman et al 53 found the proximal extension at the level of the LSA (vs arch and descending) to be associated with a higher AG rate.…”
Section: Resultsmentioning
confidence: 89%
“…Only one of these studies showed a significant association with outcomes (lower rate of AE and intervention). 45 In contrast, the proximal extension to the arch predicted both mortality and surgical intervention in two studies, 9,50 and was nonsignificant in another two. 22,37 Conversely, Kamman et al 53 found the proximal extension at the level of the LSA (vs arch and descending) to be associated with a higher AG rate.…”
Section: Resultsmentioning
confidence: 89%
“…37 Retrograde extension to involve the arch or ascending aorta confers higher risk of neurologic, cardiac, and organ malperfusion complications compared to isolated type B dissections and also warrant closer clinical monitoring (Figure 4). 19,38,39…”
Section: Reportingmentioning
confidence: 99%
“…Acute type B aortic dissection involving the aortic arch was associated with a higher rate of cardiac and neurologic complications, need for early intervention, and dissection-related death than ATBAD limited to the descending aorta [3]. Aggressive intervention was needed for patients with ATBAD involving the aortic arch [3,4]. In a recent report, 5 of 8 patients undergoing open surgical repair survived well during both the inhospital and follow-up periods, and all 3 patients treated conservatively died within 28 months [5].…”
mentioning
confidence: 95%
“…(Ann Thorac Surg 2018;106:1182-8) Ó 2018 by The Society of Thoracic Surgeons A ccording to reports of the International Registry of Acute Aortic Dissection (IRAD), acute type B aortic dissection (ATBAD) with aortic arch involvement (namely, non-A, non-B aortic dissection) is not uncommon, with an incidence as high as 16.5% to 25.5% [1,2]. Acute type B aortic dissection involving the aortic arch was associated with a higher rate of cardiac and neurologic complications, need for early intervention, and dissection-related death than ATBAD limited to the descending aorta [3]. Aggressive intervention was needed for patients with ATBAD involving the aortic arch [3,4].…”
mentioning
confidence: 99%